Keragaan Pertumbuhan dan Hasil Varietas Inpara di Lahan Rawa Pasang Surut - Koesrini, Koesrini (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2018)
The objective of this research was to evaluate the plant growth and yield of Inpara 1, 2, 3, 4, 5, 6, 7, 8, and 9 varieties in tidal swamp land with type C overflow. The research was carried out in Barambai Kolam Kanan village, Barito Kuala District, South Kalimantan Province, in theÂ dry season from April until August 2016.The research was arranged in randomized completely block design, with 3 replicates. The varieties tested i.e. Inpara 1, 2, 3, 4, 5, 6, 7, 8, 9, and check varieties (Margasari and Local). The result showed that there were variation on plant growth and yield among varieties tested. Inpara 1 and Inpara 4 yielded higher 17,7% and 31,2% than Margasari check variety and higher 18,8% and 32,4% than Local check variety. The variety of Inpara 5 is susceptable to iron toxicity and yield decreasing reaches 40.8-41.4% than both check varieties. The implication of this research was the varieties of Inpara 1 and Inpara 4 can be used as a substitute variety in the tidal swamp land with type C overflow.